Robustness in regional development studies. The case of Lithuania - Brauers, Willem Karel M.; Ginevičius, Romualdas (Journal of Business Economics and Management, 2009)
The definition of robustness in econometrics, the error term in a linear equation, was not only broadened, but, in addition, moved to the meaning of common language: from a cardinal to a qualitative one: the most robust one, more robust than…, as robust as……, robust, weak robust, less robust than…, not robust, etc. Both interpretations are tested by an application on the Robustness in Regional Development, namely of the Lithuanian Regions. The computation of Regional Income, being an exponent of the welfare economy, is not sufficient for the measurement of the well‐being of the regional population. The well‐being economy goes farther. In the well‐being economy, each individual would have to feel good concerning material wealth, health, education, all kind of security and concerning the environment. In other words, multiple objectives have to be fulfilled. Moreover, these different multiple objectives are expressed in different units. Weights are most of the time used to equalize these different units. However, introduction of weights means also introduction of subjectivity. In order to avoid this dilemma, the internal mechanical solution of a ratio system, producing dimensionless numbers, is preferred. In addition, this outcome creates the opportunity to use also a non‐subjective reference point theory. The choice of the objectives is also non‐subjective if all stakeholders are involved, or if all possible objectives are represented. This theory, which is called MOORA (Multi‐Objective Optimization by Ratio Analysis), is applied to the different regions of Lithuania. A redistribution of income has to take place from the well‐being Lithuanian regions to the poorer regions, but under limiting conditions and for well defined and eventually controlled projects. First Publish Online: 09 Jun 2011